Study of possibilities to establish regional transport terminal in Kaunas - Labanauskas, Gintautas; Palšaitis, Ramūnas (Transport, 2007)
The article describes the creation of regional transport terminals and their usage as a tool to control material flows in the distribution channels. In the first part of the article the authors analyze the role of intermodal transport terminal within international business system, legal aspects of Lithuanian and EU regulations as well as the laws of Lithuanian transport regional transport terminal establishment in Kaunas. The evaluation of alternative locations for establishment of terminal in Kaunas region is presented.First Published Online: 27 Oct 2010